Asuhan Keperawatan Pada Pasien Dengan Gangguan Konsep Diri: Harga Diri Rendah di RSUD Banyumas - Rofiq, Dwi Oka Ibnu; Trisnawati, Christina; Ningtyas, Rahaju (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Background: Mental disorders are individual maladaptive responses in the form of a group of psychotic reactions characterized by withdrawal from social life, emotional and affective disturbances which are sometimes accompanied by delusions and negative/destructive behavior. Patients with low self-esteem are at risk of developing other mental problems if they are not immediately given proper therapy, because patients with low self-esteem tend to shut themselves up and be alone, this habit triggers the emergence of other problems including social isolation. Objective: Knowing the description of nursing care in patients with impaired self-concept: low self-esteem in Banyumas Hospital using a comprehensive approach through the nursing process. Results: The results of the evaluation after carrying out nursing actions in accordance with the nursing action plan, an evaluation is carried out to find out and monitor progress and assess the level of success of the nursing actions that have been carried out on Mr. I. The results of the evaluation carried out for 3 days of mental nursing care for impaired self-concept: low self-esteem at the Banyumas Hospital in Mr. I. have not been resolved. Conclusion: Patients with low self-esteem can identify, assess, choose the positive abilities they have .